A novel minimally invasive dynamic‐shield, intensity‐modulated brachytherapy system for the treatment of cervical cancer. Issue 1 (22nd October 2020) - Morcos, Marc; Antaki, Majd; Viswanathan, Akila N.; Enger, Shirin A.
Abstract : Purpose: To present a novel, MRI‐compatible dynamicshield intensity modulated brachytherapy (IMBT) applicator and delivery system using 192 Ir, 75 Se, and 169 Yb radioisotopes for the treatment of locally advanced cervical cancer. Needle‐free IMBT is a promising technique for improving target coverage and organs at risk (OAR) sparing. Methods and materials: The IMBT delivery system dynamically controls the rotation of a novel tungsten shield placed inside an MRI‐compatible, 6‐mm wide intrauterine tandem. Using 36 cervical cancer cases, conventional intracavitary brachytherapy (IC‐BT) and intracavitary/interstitial brachytherapy (IC/IS‐BT) (10Ci 192 Ir) plans were compared to IMBT (10Ci 192 Ir; 11.5Ci 75 Se; 44Ci 169 Yb). All plans were generated using the Geant4‐based Monte Carlo dose calculation engine, RapidBrachyMC. Treatment plans were optimized then normalized to the same high‐risk clinical target volume (HR‐CTV) D90 and the D2cc for bladder, rectum, and sigmoid in the research brachytherapy planning system, RapidBrachyMCTPS. Plans were renormalized until either of the three OAR reached dose limits to calculate the maximum achievable HR‐CTV D90 and D98 . Results: Compared to IC‐BT, IMBT with either of the three radionuclides significantly improves the HR‐CTV D90 and D98 by up to 5.2% ± 0.3% ( P < 0.001) and 6.7% ± 0.5% ( P < 0.001), respectively, with the largest dosimetric enhancement when using 169 Yb followed by 75 Se and then 192 Ir. Similarly, D2cc for all OAR improved with IMBT by up to 7.7% ± 0.6% ( P < 0.001). For IC/IS‐BT cases, needle‐free IMBT achieved clinically acceptable plans with 169 Yb‐based IMBT further improving HR‐CTV D98 by 1.5% ± 0.2% ( P = 0.034) and decreasing sigmoid D2cc by 1.9% ± 0.4% ( P = 0.048). Delivery times for IMBT are increased by a factor of 1.7, 3.3, and 2.3 for 192 Ir, 75 Se, and 169 Yb, respectively, relative to conventional 192 Ir BT. Conclusions: Dynamic shield IMBT provides a promising alternative to conventional IC‐ and IC/IS‐BT techniques with significant dosimetric enhancements and even greater improvements with intermediate energy radionuclides. The ability to deliver a highly conformal, OAR‐sparing dose without IS needles provides a simplified method for improving the therapeutic ratio less invasively and in a less resource intensive manner.